Development of a Screening Method for Fluoroquinolones in Meat Samples Using Molecularly Imprinted Carbon Dots - Ahmed Faried Abdel Hakiem; Idoia Urriza-Arsuaga; Javier L. Urraca (Biosensors, 2023)
An accurate and simple screening method has been developed for the determination of fluoroquinolone antibiotics. Carbon dots were synthesized by simple hydrothermal treatment as highly fluorescent nano-sensors. They were subsequently used in the synthesis of organic-based molecularly imprinted polymers to develop fluorescence-based polymeric composites using enoxacin as a representative dummy template molecule of fluoroquinolones. The method was optimized concerning the pH of the medium and composite concentration. The normalized fluorescence intensity showed efficient quenching under optimized conditions upon successive addition of the template, with an excellent correlation coefficient. The proposed method was applied to eight other fluoroquinolones, exhibiting, in all cases, good correlation coefficients (0.65–0.992) within the same linearity range (0.03–2.60 mg mL−1). Excellent detection and quantification limits were been obtained for the target analytes down to 0.062 and 0.186 mg L−1, respectively. All studied analytes showed no interference with enrofloxacin, the most commonly used veterinary fluoroquinolone, with a percentage of cross-reactivity varying from 89.00 to 540.00%. This method was applied successfully for the determination of enrofloxacin in three different types of meat samples: beef, pork, and chicken, with good recoveries varying from 70 to 100% at three levels. This new procedure is an easy analytical method that can be useful as a screening method for monitoring the environmental hazard of fluoroquinolones in quality control laboratories.